Formulasi Tablet salut Teofilin Menggunakan Eksipien Koproses Pregelatinisasi pati Singkong- Metilselulosa sebagai bahan Penyalut - Pradana, Rangga; Chaidir, Chaidir; Anwar, Effionora (Majalah Ilmu Kefarmasian, 2010)
Pregelatinized cassava star ch (PCS) is a physically modified starch. The purposes of the study were to improve functionality of PCS with making coprocess composed of PCS and methylcellulose (MC) by proportionally variation, which are 2:1, 3:1, and 4:1, as well as to applied co-processed excipient that could retard the drug release as coating material of theophylline tablet. Coprocessed excipient were characterized in terms of morphology, particle size distribution, compressibility index, flow rate and angle of repose, thermal analysis, hygroscopicity, gel strength, swelling test, and moiety analysis. Theophylline tablet that coated by PCS, MC, and co-processed PCSMC ratio (4:1) characterized and in vitro drug release were made in chloride medium of pH 1,2 and phosphate medium of pH 7,2. The characterization result of co-processed PCS-MC showed the improvement of functionality from PCS and synergism PCS with MC. Meanwhile, the result of in vitro drug release showed theophylline tablet that coated by MC 1%, co-processed PCS-MC (4:1) 4% and 2% could retard the drug release in both medium.